Development of Augmented Reality to Solve Geometry HOTS Problems for Class V SDN 1 Doplang Students - Ahmad Ridlo Setiawan; Nursiwi Nugraheni (JETL (Journal of Education, Teaching and Learning), 2025)
The results of the initial interview were explained by the class teacher that grade V students of SDN 1 Doplang still had difficulty doing high-level questions, especially on geometry material. Then the observations also prove that in general, teachers still use models and learning media only in the form of pictures and videos. The purpose of this study is to develop augmented reality learning media based on geobar applications so that it can facilitate students in the process of understanding geometry material. The type of research used is research and development (RnD) with the Borg and Gall model which is modified into 9 stages. Data collection techniques through observation, interviews, questionnaires, and documentation. Results of the product assessment are in the form of validation of learning media carried out by material, media, and language experts with percentages of 91.6%, 90.6%, and 93.1% with a classification of "very feasible". The effectiveness of media with the T-Test obtained a signification value of 0.000. The result of the N-gain calculation was found to be 0.6904 with the criterion "medium". So the learning media for geobar applications of geometry material can be said to be very feasible and effective to be applied in improving the ability to solve hots problems. Researchers recommend the development of augmented reality (AR) media so that it can continue to be maximized so that the learning process can take place interesting and fun so that the material delivered can be easily understood by students.